Pemodelan perhitungan biaya pengadaan persediaan bahan baku menggunakan metode EOQ di perusahaan kosmetika - I Gusti Ngurah Agung Dewantara; N. P. A. D. Wijayanti; A. A. Yastawa (DiscoverSys Inc., 2017)
Background: The process of procurement of supplies is a very important in manufacturing company, without supplies, the company will face a difficult continuity of the production process. Aim: This research is to compare the amount of raw material purchase, frequency of purchase of raw materials, the frequency of delivery of raw materials, and the total cost of procurement of raw material inventories carried out using traditional methods and modeling methods EOQ in Cosmetics Company. Method: Data were collected using the data of the company in 2014-2015 and interviews with the owners and employees of the Company Cosmetics. Results: From this research is obtained the comparison of traditional methods and modeling EOQ ie the amount of raw material purchases in one message 1000kg: 8.440kg increased by 8.44 times, frequency of purchase of raw materials 24: 6 times, frequency of delivery of raw materials 24: 6 times. Conslusions: Total savings cost of raw material inventory control 70% of the total cost of procurement of raw material inventory by the company using traditional methods.